2021
DOI: 10.1002/acr.24256
|View full text |Cite
|
Sign up to set email alerts
|

Illness Experiences of Chilean Women With Sjögren’s Syndrome: The Patient Perspective

Abstract: Objective Sjögren’s syndrome (SS) challenges everyday functioning and well‐being. The aim of this study was to structure and summarize the life experiences of Chilean women with SS in an integrated model. Methods Interviews from a previous study yielded 75 experiences of living with SS. A sample of 30 women with SS sorted these experiences by content and rated their level of agreement with each experience. A hierarchical cluster analysis was used to structure the experiences of the participants with SS in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In a recent study about SS experiences in Chilean women, ten clusters were identified, arranged in six main categories: ‘Symptoms’ (clusters: ‘Mucosal dryness’ and ‘Related symptoms’), ‘Social environment’, ‘Emotion management’ (clusters: ‘Fears’ and ‘Sadness’), ‘Information’ (clusters: ‘Uncertainty’ and ‘Lack of knowledge’), ‘Coping strategy’ (clusters: ‘Resilience’ and ‘Self-care’), and ‘Health staff relationship’ [ 10 ]; these clusters are similar to those of our study, but two new clusters emerged, the Internet as a source of information and sexuality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study about SS experiences in Chilean women, ten clusters were identified, arranged in six main categories: ‘Symptoms’ (clusters: ‘Mucosal dryness’ and ‘Related symptoms’), ‘Social environment’, ‘Emotion management’ (clusters: ‘Fears’ and ‘Sadness’), ‘Information’ (clusters: ‘Uncertainty’ and ‘Lack of knowledge’), ‘Coping strategy’ (clusters: ‘Resilience’ and ‘Self-care’), and ‘Health staff relationship’ [ 10 ]; these clusters are similar to those of our study, but two new clusters emerged, the Internet as a source of information and sexuality.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the participants categorized the cards into piles using similarity of content and gave each pile a label. To better understand the concept mapping technique and the procedure used in our study, consult previous research [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some findings of our study are in line compared with other qualitative studies in pSS. We already know that the patients with pSS are confronted with a long way until diagnosis and thoughts about the origin of the disease and also the consequences of the disease on the physical, emotional, and social level ( 7 , 33 , 35 , 36 , 46 , 47 ). We also know from other studies in pSS ( 33 ) and other rheumatic conditions that the patients sometimes feel that they are not taken seriously or that their complaints are dismissed by the health professionals ( 33 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…We already know that the patients with pSS are confronted with a long way until diagnosis and thoughts about the origin of the disease and also the consequences of the disease on the physical, emotional, and social level ( 7 , 33 , 35 , 36 , 46 , 47 ). We also know from other studies in pSS ( 33 ) and other rheumatic conditions that the patients sometimes feel that they are not taken seriously or that their complaints are dismissed by the health professionals ( 33 , 46 ). The participants of our study specifically felt that the time the health personnel spent with them was insufficient.…”
Section: Discussionmentioning
confidence: 99%